P057: Diagnosis for mild traumatic brain injury in three Canadian emergency departments: missed opportunities. (15th May 2017) - Gaudet, L.; Eliyahu, L.; Lowes, J.; Beach, J.; Mrazik, M.; Cummings, G.; Latoszek, K.; Carroll, L.; Holroyd, B.R.; Rowe, B.H.
Abstract : Introduction: Patients with mild traumatic brain injury (mTBI) often present to the emergency department (ED). Incorrect diagnosis may delay appropriate treatment and recommendations for these patients, prolonging recovery. Notable proportions of missed mTBI diagnosis have been documented in children and athletes, while diagnosis of mTBI has not been examined in the general adult population.Methods: A prospective cohort study was conducted in one academic (site 1) and two non-academic (sites 2 and 3) EDs in Edmonton, Canada. On-site research assistants enrolled adult (>17 years) patients presenting within 72 hours of the injury event with clinical signs of mTBI and Glasgow comma scale score ≥13. Patient demographics, injury characteristics, and ED flow information were collected by chart review. Physician-administered questionnaires and patient interviews documented the recommendations given by emergency physicians at discharge. Bi-variable comparisons are reported using Pearson's chi-square tests, Student's t-tests or Mann-Whitney tests, as appropriate. Multivariate analyses were performed using logistic regression methods.Results: Overall, 130/250 enrolled patients were female, and the median age was 35. Proportions of successfully diagnosed mTBI varied significantly across study sites (Site 1: 89%; Site 2: 73%, Site 3: 53%; p>0.001). Patients without a diagnosis were less likely to receive a recommendation to follow-up with their family physician (OR=0.08; 95% CI: 0.03, 0.21) or advice about return to work (OR=0.17; 95% CI: 0.08, 0.04) or physical activity (OR=0.08; 95% CI: 0.04, 0.17). Patients with missed diagnoses had longer ED stays (median=5.0 hours; IQR: 3.8, 7.0) compared with diagnosed mTBI patients (median=3.9 hours; IQR: 3.0, 5.3). In the adjusted model, patients presenting to non-academic centers had reduced likelihood of mTBI diagnosis (Site 2: OR=0.21; 95% CI: 0.08, 0.58; Site 3: OR=0.07; 95% CI: 0.02, 0.24).Conclusion: The diagnostic accuracy of physicians assessing patients presenting with symptoms of mTBIs to these three EDs is suboptimal. The rates of missed diagnosis vary among EDs and were associated with length of ED stay. Closer examination of institutional factors, including diagnosis processes and personnel factors such as physician training, is needed to identify effective strategies to heighten the awareness of mTBI presentations.